Research into rock pressure manifestations in interstratal rocks during descending and simultaneous mining of C₉ and C₁₀Top coal seamsResearch into rock pressure manifestations in interstratal rocks during descending and simultaneous mining of C₉ and C₁₀Top coal seams - Kovalevska, I.; Symanovych, H.; Barabash, M.; Snihur, V. (Розробка родовищ, 2017)
Purpose. To estimate the probability of interstratal rocks stability loss during simultaneous mining of two seams in series in the descending order. Findings. Recommendations for the improvement of 914 bolting system parameters of complex roadway for possibility of its reusing are developed. Originality. Regularity of stress-strain state change of parting during simultaneous mining of coal seams with the purpose to reveal the constituent of rock pressure manifestations during the top seam mining is studied. Цель. Оценка вероятности потери устойчивости пород междупластья при одновременной отработке двух пластов в свите в нисходящем порядке. Результаты. Разработаны рекомендации по совершенствованию параметров крепежной системы 914 сборного штрека для обеспечения возможности его повторного использования. Научная новизна. Изучена закономерность изменения напряженно-деформированного состояния междупластья при одновременной отработке угольных пластов с целью выявления составляющей проявлений горного давления при отработке верхнего пласта. Мета. Оцінка ймовірності втрати стійкості порід міжпластя при одночасному відпрацюванні двох пластів у свиті в низхідному порядку. Результати. Розроблено рекомендації щодо вдосконалення параметрів кріпильної системи 914 збірного штреку для забезпечення можливості його повторного використання. Наукова новизна. Вивчено закономірність зміни напружено-деформованого стану міжпластя при одночасному відпрацюванні вугільних пластів з метою виявлення складової проявів гірського тиску при відпрацюванні верхнього пласта.